Three-Dimensional Modeling and Augmented and Virtual Reality Simulations of the White Matter Anatomy of the Cerebrum. Issue 5 (28th November 2022) - Gurses, Muhammet Enes; Gungor, Abuzer; Gökalp, Elif; Hanalioglu, Sahin; Karatas Okumus, Seda Yagmur; Tatar, Ilkan; Berker, Mustafa; Cohen-Gadol, Aaron A.; Türe, Uğur
Abstract : BACKGROUND: An understanding of the anatomy of white matter tracts and their 3-dimensional (3D) relationship with each other is important for neurosurgical practice. The fiber dissection technique contributes to this understanding because it involves removing the brain's white matter tracts to reveal their anatomic organization. Using this technique, we built freely accessible 3D models and augmented and virtual reality simulations of white matter tracts. OBJECTIVE: To define the white matter tracts of cadaveric human brains through fiber dissection and to make 2-dimensional and 3D images of the white matter tracts and create 3D models and augmented and virtual reality simulations. METHODS: Twenty cadaveric brain specimens were prepared in accordance with the Klingler method. Brain hemispheres were dissected step-by-step from lateral-to-medial and medial-to-lateral directions. Three-dimensional models and augmented reality and virtual reality simulations were built with photogrammetry. RESULTS: High-resolution 3D models and augmented reality and virtual reality simulations of the white matter anatomy of the cerebrum were obtained. These models can be freely shifted and rotated on different planes, projected on any real surface, visualized from both front and back, and viewed from various angles at various magnifications. CONCLUSION: To our knowledge, this is the first detailed study integrating various technologies (3D modeling, augmented reality, and virtual reality) for high-resolution 3D visualization of dissected white matter fibers of the entire human cerebrum.